Unwritten history - Dow, Helen Pearl (My University, 1891)
Introduction: History is a record of past events the world’s diary in which has been written the rise and decay of nations. Of all mankind there is no tribe so barbarous but what has in some form recorded its history. History therefore has been written in many ways, by means of rude pictures, hieroglyphics, earth mounds, and monumental stone heaps. But the history of nations is the history of the individuals constituting them. Nations are made what they are by the thinking and working of many generations. Battles and tumults which for the time die every ear pass away. Rome was not built in a day nor is the history of a nation made complete by the booming of cannon or by the result of a battle. It has not been the work of great events only but the accumulated teachings of many generations of men. The discovery by Columbus was but the beginning of the modern history of America. It alone did not make it. The record was carried down to our forefathers in whose hearts were so firmly implanted the belief that all men were born free and equal and who risked their property, their lives, their all in order that the world might reap the benefits from their struggle for liberty.
Citation: Dow, Helen Pearl. Unwritten history. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: History; Historical record; Theses; Manuscripts (documents)